(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Defined as a piggyback basin, the Plio-Pleistocene Sant’Arcangelo basin is one of the more recent onshore sedimentary basin of the Southern Apennines. Extensive field studies allow to reinterpret the whole stratigraphy of the basin in a more simple and significant way. Five unconformity-bounded units ("groups") have been recognised : The (1) Catarozzo Group (late Pliocene) unconformably overlies pre-Miocene units, and it is composed of a flood-dominated fan-delta marine (C1) and restricted-marine (C2) systems bounded by a sharp contact with a total thickness up to 650 meters. The (2) Aliano Group (late Pliocene - early Pleistocene) includes an up to 1,400 meters thick succession of flood-dominated fan-delta systems, with facies ranging from poorly organised alluvial conglomerates in the west to massive marine mudstones in the east. Two sub-units have been recognised, bounded by a regional unconformity, which shows an abrupt passage from marine (A1) to restricted-marine (A2) conditions. The (3) Tursi Group (early-middle Pleistocene) reaches a thickness of 500 meters. It is composed of two sub-units, corresponding to alluvial fan (T1) and fan-delta (T2) systems. The alluvial facies of T2 (conglomerates) outcrop extensively in the Sant’Arcangelo basin, with equivalent flood-dominated shelfal sandstone lobes broadly developed in the Tursi area (Metaponto basin). The (4) Profico and (5) Montalbano Jonico groups (middle Pleistocene) are partially time equivalents, and were developed in both sides of the Valsinni structure, which divided an early, broader Sant’Arcangelo basin into two sub-basins, the present "Sant’Arcangelo" and "Metaponto" basins. The Profico Group has a thickness of up to 300 m and consists of lacustrine strata overlying in angular unconformity the Tursi Allogroup in the "Sant’Arcangelo basin". The Montalbano Jonico Group on the other hand is made up of up to 300 m of fine-grained marine strata unconformably overlying the Tursi Group in the "Metaponto basin". All the units considered display clear evidences of synsedimentary tectonics.